Best practices protocol for the evaluation of bulbar dysfunction: summary recommendations from the NEALS bulbar subcommittee symposium. Issue 3 (3rd April 2018) - Pattee, Gary L.; Plowman, Emily K.; Brooks, Benjamin R.; Berry, James D.; Atassi, Nazem; Chapin, Jennifer L.; Garand, Kendrea; Yunusova, Yana; Mcilduff, Courtney E.; Young, Eufrosina; Costello, John M.; Macklin, Eric A.; et al.
Abstract: Objective : The aim of this Symposium was to develop a consensus based, bulbar assessment protocol for implementation within NEALS clinics. Methods : A one-day symposium, held in April 2017, was organized into Speech and Swallowing sections to establish summary recommendations for the assessment of bulbar dysfunction within each group. Results : Summary recommendations included speech referrals and AAC evaluations at initial visit, CNS-BFS, maximum sustained phonation, and speaking rate. Dysarthria evaluation included the speech subsystem involvement of respiration, phonation, resonance, and articulation. Specific recommendations for swallowing were established for each of the following domains: dietary/oral intake, airway defense physiologic capacity, swallow safety screen, patient-reported swallow-related outcomes, oral sensorimotor exam, and pulmonary function. Practice parameters focused upon patient education and unresolved questions included the use of videofluoscopy, monitoring diet progression, and swallow safety screening. Conclusions : The working goal is to establish a clinical bulbar protocol, designed to be incorporated within ALS clinics and ultimately to formulate a best practice set of bulbar ALS guidelines, available for implementation throughout the international ALS community.